Models of “happiness” – A South African perspective - Naudé, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
This article explains the complex notion of “happiness” and the variety of theological approaches to happiness. It then sketches three models of happiness in the South African context: the segregation model deriving from a specific understanding of neo-Calvinism, the traditional African model based on a communitarian notion of ubuntu, and the model stemming from modernity with its emphasis on individuality and rationality. The last section is not fully developed and only outlines a Christian and Biblical understanding of happiness with emphasis on joy in the Lord that stems from both the wisdom traditions and the New Testament letters.